Peningkatan Branding Wisata Puncak Watu Wayang Melalui Program Kerja Unggulan KKN-T : Fun Trailing Mobile Remote Control Adventure - Rosiana Puspitasari, Dyah; Fara Rinanti; Fakhry Muhammad Ibrahim; Naufal Kusuma Yudha; Raden Roro Caturini Putranti Kusumaningrum; Randi Gunawan; Ade Komo Purnomo; Delti Narei; Sekar Ladita; Avvan Baykhaqi Amsar; Rifki Indra Jaya; Muhammad Desfri Gunadi (Swadaya: Jurnal Pengabdian Masyarakat, 2024)
This community service aims to address the issues of tourism conditions and promotion faced by Puncak Watu Wayang Tourism, Duwet Gentong, Srimulyo, Piyungan, Bantul, Special Region of Yogyakarta. The method used in this community service activity is participatory observation. The community service team observes and participates in daily activities, interacts with local residents, and records what they see and do. The dynamics of the rehabilitation process and the programs to be implemented in tourism are obtained through this participatory observation method. The result of this development program is an increase in tourist comfort through the improvement of tourist destinations, as well as the Fun Trailing Mobile Remote Control Adventure event, which allows for broader tourism promotion.